Dam removal enables diverse juvenile life histories to emerge in threatened salmonids repopulating a heterogeneous landscape - Munsch, Stuart H.; McHenry, Mike; Liermann, Martin C.; Bennett, Todd R.; McMillan, John; Moses, Raymond; Pess, George R. (Frontiers in Ecology and Evolution, 2023)
Human stressors block, eliminate, and simplify habitat mosaics, eroding landscapes’ life history diversity and thus biological resilience. One goal of restoration is to alleviate human stressors that suppress life history diversity, but life history responses to these efforts are still coming into focus. Here, we report life history diversity emerging in threatened salmonids (Oncorhynchus spp.) repopulating the recently undammed Elwha River (WA, USA) in adjacent but environmentally distinct tributaries. The ~20 km tributaries entered the Elwha River <1 km apart, but one had a colder stream temperature regime and swifter waters due to its high, snow-dominated elevation and steep valley gradient (~3%), while the other had a warmer stream temperature regime and slower waters because it drained a lake, was at lower elevation, and had a lower stream gradient (~1.5%). Following the 2012 removal of Elwha Dam, the tributaries’ salmonids generally became more abundant and expressed diverse life histories within and among species. The warmer, low-gradient tributary produced more age-1+ coho salmon while the colder, steeper tributary produced a notably high abundance of steelhead smolts in 2020. Additionally, salmonids exiting the warmer tributary were older and possibly larger for their age class, emigrated ~25 days earlier, and included age-0 Chinook salmon that were larger. Also, assemblage composition varied among years, with the most abundant species shifting between Chinook salmon and coho salmon, while steelhead abundances generally increased but were patchy. These patterns are consistent with a newly accessible, heterogeneous landscape generating life history diversity against the backdrop of patchy recruitment as salmonids – some with considerable hatchery-origin ancestry – repopulate an extirpated landscape. Overall, dam removal appears to have promoted life history diversity, which may bolster resilience during an era of rapid environmental change and portend positive outcomes for upcoming dam removals with similar goals.